2011
DOI: 10.15664/jtr.189
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food Consumption, Government Type and Effectiveness, on the Rate of Somali Maritime Piracy, 2000-2008

Abstract: The analysis of maritime piracy off the Horn of Africa is still a developing area of academic research. The work that has been conducted to date has remained largely qualitative. Two recurring assumptions made but not empirically tested in this area of research are 1) the perceived link between government stability and the rate of maritime piracy, and 2) drought conditions implying food shortages in Somalia, and their impact on the rate of maritime piracy off the Horn of Africa The findings of this project sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…It is often suggested that state collapse and the removal of governmental authority as occurred in Somalia during the 1990s is a precondition for pirate activity (Korteweg, 2008; Verhoeven, 2009). The logical extension of this analysis, is that ‘the war against piracy is one on land’, which translates into rebuilding government structures in Somalia (Boot, 2009; Kraska, 2010; Kraska and Wilson 2008/9; Menkhaus, 2007; Rohrer, 2011). The work by international partners, such as the UN agencies or the African Union, is therefore focused on building up the Transitional Federal Government of Somalia, even though its authority is limited to a small section of Mogadishu and even there upheld by foreign troops and treasure.…”
mentioning
confidence: 99%
“…It is often suggested that state collapse and the removal of governmental authority as occurred in Somalia during the 1990s is a precondition for pirate activity (Korteweg, 2008; Verhoeven, 2009). The logical extension of this analysis, is that ‘the war against piracy is one on land’, which translates into rebuilding government structures in Somalia (Boot, 2009; Kraska, 2010; Kraska and Wilson 2008/9; Menkhaus, 2007; Rohrer, 2011). The work by international partners, such as the UN agencies or the African Union, is therefore focused on building up the Transitional Federal Government of Somalia, even though its authority is limited to a small section of Mogadishu and even there upheld by foreign troops and treasure.…”
mentioning
confidence: 99%